Answer :

Given the equation x2 - kx + 1 = 0 has no real roots


a = 1 b = - k c = 1


Thus D = b2 - 4ac < 0


( - k)2 - 4.1.1 < 0


k2 - 4 < 0


k2 < 4


- 2 < k < 2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses